Bio-economy Sustainable Agriculture Strategy In Cirebon Regency - Nurjanah, Irma (Ann Publisher, 2024)
The production of national agricultural products in the last 10 (ten) years has fluctuated and tends to decrease. Burning straw waste in rice fields contributes to greenhouse gas emissions, known as one of the causes of global warming that will decrease the quality and quantity of natural resources and impact the decline in agricultural product production. Analyzing these problems, the author conducted a literature review to find good practices based on the latest study's results. The results show that the bio-economy as part of agriculture can be a strategy to mitigate the impact of climate change to support sustainable agriculture. The bio-economy will manage waste into valuable products while reducing dependence on fossil fuels and minimizing environmental impact. To support this, the Regional Head and the Cirebon Regency legislature must draft a regional regulation on the prohibition of burning rice straw waste to support the reduction of greenhouse gas emissions.